The Status of Antibiotics (Res Medica, 2013)
From a dissertation read before the Royal Medical Society on Friday, 1st November, 1963.Many attribute the earliest recognition of an antibiotic effect to Sir Alexander Fleming. However, in 1877, 50 years before Fleming’s discovery, Pasteur and Joubert described the phenomenon of bacterial antagonism; the process whereby the growth of certain species is inhibited in the presence of others. In the particular case of the anthrax bacillus they found that growth was inhibited in cultures contaminated with ‘common bacteria’ (those types now known as the Enterobacteriaciae). Shortly afterwards the term “antibiosis” was introduced for such antagonism.